Introduction to the two FICE 2020 Special Issues - Grupper, Emmanuel; Schneider, Alexander; Peters, Friedhelm (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
FICE International is an international organization focused on children and youth who are in need of out-of-home care. One of its major activities is organizing a world congress every three years. In these congresses, professionals from all over the world who are involved with out-of-home care can meet, exchange knowledge, and learn from each other. The most recent FICE congress, held in October 2019 in Tel Aviv, Israel, was dedicated to the theme “Better Future Opportunities for Children and Young People in Multicultural Societies”. The editor of this journal has been kind enough to offer this platform for the publication of selected material presented at the congress. FICE-International, and we as guest editors, are most thankful to Prof. Sibylle Artz, editor of the IJCYFS, for this opportunity. The richness and variety of the selected articles, coming from 10 countries, could not be accommodated in a single issue. The editors of the journal have therefore decided to divide the articles into two special issues, to be published one after the other. The first of these issues includes articles in three thematic categories: (a) Evidence-based research on effects of out-of-home care, (b) Historical and sociological perspectives on institutionalized child and youth care, and (c) Normalization — a challenge for foster care programs. Four further categories will provide the framework for the forthcoming second special issue: (d) Emotional and pedagogical considerations, (e) Refugee children and youth, (f) Residential staff, and (g) Care leavers.